2016
DOI: 10.1017/s1352465816000448
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Worry and Dimensions of Anxiety Symptoms in Children and Adolescents

Abstract: Background Worry is a common feature across many anxiety disorders. It is important to understand how and when worry presents from childhood to adolescence to prevent long-term negative outcomes. However, most of the existing studies that examine the relationship between worry and anxiety disorders utilize adult samples. Aims The present study aimed to assess the level of worry in children and adolescents and how relationships between worry and symptoms of separation anxiety disorder (SAD) and social anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
1
11
1
Order By: Relevance
“…A further striking pattern observed in the data was the degree of variation in ratings of anxiety and worryemotions which are often used interchangeably when discussing climate-related emotions. Worry is a primary feature of anxiety and anxiety disorders(Newman et al, 2013;Rabner et al, 2017). However, a smaller proportion of people reported that they felt 'very' or 'extremely' Contrary to our hypothesis (H1), negative climate-related emotions were not significantly related to the overall rate of exposure to climate change-related media (Table3).…”
contrasting
confidence: 71%
“…A further striking pattern observed in the data was the degree of variation in ratings of anxiety and worryemotions which are often used interchangeably when discussing climate-related emotions. Worry is a primary feature of anxiety and anxiety disorders(Newman et al, 2013;Rabner et al, 2017). However, a smaller proportion of people reported that they felt 'very' or 'extremely' Contrary to our hypothesis (H1), negative climate-related emotions were not significantly related to the overall rate of exposure to climate change-related media (Table3).…”
contrasting
confidence: 71%
“…Again consistent with the findings of Hodson et al ( 2008 ), pre-event processing was found to be an independent predictor of depression but not social anxiety in regression analyses. A correlational study of 60 adolescents with an anxiety disorder diagnosis (Rabner et al 2017 ) found a significant correlation between self-reported social anxiety symptoms and worry ( r = 0.432), as measured by the Penn State Worry Questionnaire (Chorpita et al 1997 ).…”
Section: A Review Of Studies Examining the Applicability Of The Cognimentioning
confidence: 99%
“…Anxiety or fear, as well as worry, are present in all anxiety-related disorders [ 169 , 170 ]. Anxiety symptoms are mainly associated with dysfunctional amygdala-centred circuits whereas worry symptoms are connected with cortico-striato-thalamocortical (CSTC) loop dysfunctions, both involving disturbances of 5-HT and gamma-aminobutyric acid (GABA) [ 83 ].…”
Section: The Association Between Stress Inflammation and Treatment Rmentioning
confidence: 99%